PENINGKATAN KREATIVITAS DAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE-STAD TERINTEGRASI ICT - Rangkuti, Rizki Kurniawan; Ramli, Marwan; Nasution, Mulkan Iskandar (Program Studi Pendidikan Matematika FTIK IAIN Langsa, 2019)
This research was conducted for 2 weeks in October at SMAN 11 Medan. This type of research is classroom action research. Before the action is taken first, the initial test is given. From the results of the initial test, the average student achievement was 20.62 with a classical completeness level of 0%. After giving action I to creative thinking tests the level of student study in classical is 15%, with an average grade achievement of 33.75. To test student learning outcomes the level of completeness obtained by students is 17.5%, with an average grade achievement of 26.42. After the implementation of action II for creative thinking tests the level of student study learning in classical is 85%, with an average achievement of 72.85 classes. To test student learning outcomes the level of completeness obtained by students is 90%, with an average grade achievement of 77.17. From this there is an increase in the level of classical completeness by 70% for students 'creative thinking and 72.5% for students' mathematics learning outcomes. Keywords: Mathematical Creativity, Mathematics Learning Outcomes, ICT Media, Cooperative Type-STAD Model.